Fabrication of electroactive multi-layered polyazulene thin films by atmospheric pressure-vapor phase polymerization - Yewale Rahul; Damlin Pia; Suominen Milla; Kvarnström Carita (Elsevier Science SA, 2022)
Thin films of polyazulene (PAz) are produced by using an optimized atmospheric pressure–vapor phase polymerization (AP-VPP) method. Method optimization is carried out by studying the effect of cell temperature, substrate temperature, polymerization time, and washing-solvent on film properties like optical bandgap, sheet resistance, surface roughness, and % transmittance (%T). Multi-layered PAz films were produced by layer-by-layer engineering. The effects of thin, electroactive multiple layers on film properties are investigated. UV–Vis, IR, and Raman analysis are utilized to understand the extended conjugation length and nature of the charge carriers. The spectroscopic data revealed the anomalous behaviour of PAz at a high level of doping. The proportion and amount of quinoid conformation is discussed. The addition of layers changes the transport of ions across the electroactive PAz films, which is studied using cyclic voltammetry at various scan rates. AFM and SEM images reveal a change in structural properties which is further correlated with a deviation of capacitance values at elevated scan rate. Comparison with earlier reported literature on electrochemically and chemically synthesized PAz is also provided. The conductivity, transparency and high capacitance show a promising application of AP-VPP PAz in various fields.